2018
DOI: 10.1002/jmri.25929
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modified two‐point dixon and chemical shift encoded MRI water‐fat separation methods for fetal fat quantification

Abstract: 4 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Other than CSE-MRI, a couple of other MRI sequences could also facilitate better characterization of fatty lesions, Dixon sequences rely on the difference in resonance frequency between water and fat, unlike fat suppression sequences. Hence, Dixon sequences could generate water-only, fat-only, in-phase and out-of-phase images in a single acquisition ( 13 , 14 ). Kuetting et al used multipoint Dixon technique to non-invasively distinguish chylous and nonchylous ascites and pleural effusions ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other than CSE-MRI, a couple of other MRI sequences could also facilitate better characterization of fatty lesions, Dixon sequences rely on the difference in resonance frequency between water and fat, unlike fat suppression sequences. Hence, Dixon sequences could generate water-only, fat-only, in-phase and out-of-phase images in a single acquisition ( 13 , 14 ). Kuetting et al used multipoint Dixon technique to non-invasively distinguish chylous and nonchylous ascites and pleural effusions ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently used in clinical applications, while the dual‐echo Dixon sequence is more widely available on clinical systems. These two sequences were shown to have comparable reliability in fat quantification 38 . Compared to acquisition with two TEs, the multiecho Dixon method typically acquires six TEs thus results in lower SNR/resolution and/or longer scan time, which is a large disadvantage in abdominal imaging due to severe motion 39 .…”
Section: Discussionmentioning
confidence: 99%
“…These two sequences were shown to have comparable reliability in fat quantification. 38 Compared to acquisition with two TEs, the multiecho Dixon method typically acquires six TEs thus results in lower SNR/resolution and/or longer scan time, which is a large disadvantage in abdominal imaging due to severe motion. 39 In addition, the fundamental contrast differences between dual-echo Dixon and multiecho Dixon sequences is another important factor that the multiecho Dixon images were not included in this study but to further promote this DL-based method in clinical applications, training, and testing on the multiecho Dixon images is inevitable in the next steps.…”
Section: Limitationsmentioning
confidence: 99%
“…While this sequence has recognized limitations of sensitivity to T2* effects (caused by e.g. iron) and incomplete fat spectrum modelling (MRI fat signal at multiple frequencies due to the complex chemical structure of triglyceride) [34], recent work has demonstrated that these effects do not cause bias in estimates of fat fraction with modified 2point Dixon in fTSAT [35]. However it should be noted that Giza et al did demonstrate biases in estimates of fat fraction with modified 2-point Dixon in other tissues including the liver [35].…”
Section: Discussionmentioning
confidence: 99%